Comparing CO2 and Variable-TDS Waste-Fluid Injection Into Deep Saline Geologic Formations - Ansari, Esmail; Holubnyak, Eugene; Hasiuk, Franciszek; Raney, Jennifer (Frontiers in Energy Research, 2022)
There is a renewed interest in carbon capture, utilization, and storage technology due to recently expanded US Internal Revenue Service 45Q credits as well as to reduce anthropogenic carbon emissions to the atmosphere. Deep carbonate reservoirs in western Kansas have the potential for CO2 storage because they have experienced low waste-fluid injection volumes to date. Waste-fluid injection in Kansas has not caused felt seismicity for more than seven decades. However, beginning in 2013, the state has experienced increased seismicity due to increased subsurface pressure associated with the injection of large volumes of variable-TDS (total dissolved solids) waste-fluid in US EPA Class I and Class II wells. This work compares CO2, low-TDS, and high-TDS injection practices and quantifies the induced spatial and temporal patterns in overpressure in the caprock, reservoir, and its hydraulically connected crystalline basement, where the majority of induced seismicity in Kansas has been observed. Our results show that pressure buildup is higher in the caprock and lower in the crystalline basement when injecting CO2 as compared to variable-TDS waste-fluid injection. The CO2 plume tends to expand at the top of the reservoir, primarily due to its lower density and viscosity than reservoir brines, creating an overpressure plume that moves the resident brine across the caprock. In contrast, waste-fluid injection moves more resident brine down into the basement, particularly when high-TDS waste-fluid is injected. This result is particularly valid for high-permeability carbonate reservoirs, in which gravity forces dominate over viscous forces and move the CO2 and overpressure plume toward the top of the reservoir. Our study may explain the lack of human-perceivable induced seismicity at operating CO2 injection projects globally.